1998
DOI: 10.1210/jc.83.11.3890
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prospective Study of Body Composition and Lipid Profiles during and after Growth Hormone (GH) Treatment in Children with GH Deficiency: Gender-Specific Metabolic Effects

Abstract: GH has many effects on metabolism in addition to promoting growth. We studied changes in body composition and lipid profiles during and after GH treatment in 94 children with GH deficiency. Sixty-two subjects (46 boys and 16 girls) were evaluated at the beginning and during 36 months of GH treatment. The other 32 (21 boys and 11 girls) who had already been treated with GH were examined after the discontinuation of GH for a 6-month period. The height SD scores at the beginning and the discontinuation of GH trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 0 publications
9
65
3
Order By: Relevance
“…Estrogen has effects on body composition in girls during adolescent period and afterwards (Austin et al, 1991;Butte et al, 1997). Growth hormone treatment induces reduction of body fat (Kuromaru et al, 1998) and lower serum leptin levels (Elimam et al, 1999). Concerning significant correlation between leptin and %Wt in normal-weight girls, estrogen does not Figure 4 Relation between serum leptin levels and %Wt in normalweight girls.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has effects on body composition in girls during adolescent period and afterwards (Austin et al, 1991;Butte et al, 1997). Growth hormone treatment induces reduction of body fat (Kuromaru et al, 1998) and lower serum leptin levels (Elimam et al, 1999). Concerning significant correlation between leptin and %Wt in normal-weight girls, estrogen does not Figure 4 Relation between serum leptin levels and %Wt in normalweight girls.…”
Section: Discussionmentioning
confidence: 99%
“…GH has complex effects on lipid metabolism (19) and it may be that cholesterol levels varied during GH treatment while attaining a new equilibrium state. In Japanese children with GHD, who have been treated with GH, mean total cholesterol and total/high-density-lipoprotein-cholesterol ratio were decreased markedly in both sexes but statistical significance was detected only in boys (20). The longest-term data in Japanese paediatric male GHD patients showed that 3 years of GH replacement caused a significant decrease in LDLcholesterol (21).…”
Section: Incidence Of Adverse Events N (% Of N)mentioning
confidence: 98%
“…This method has been validated previously and within-day and between-day measurements have been reported to have high reproducibility. 27,28 Biochemical and hormonal analyses Venous blood samples were taken after an overnight fast between 8 and 9 a.m. All biochemical analyses including glucose, total cholesterol, and triglyceride concentrations were performed with a technicon DAX-72 autoanalyser (Technicon, Bayer Corporation, Tarrytown, New York) in the Central Biochemistry Laboratory, Istanbul Faculty of Medicine. HDL cholesterol concentrations were also measured at the RA-XT autoanalyser after phosphotungstic acid and magnesium chloride precipitation.…”
Section: Body Compositionmentioning
confidence: 99%